Behavior of Tilted Angle Shear Connectors - Khorramian, K.; Maleki, S.; Shariati, M.; Sulong, N.H.R. (Public Library of Science, 2015)
According to recent researches, angle shear connectors are appropriate to transfer longitudinal shear forces across the steel-concrete interface. Angle steel profile has been used in different positions as L-shaped or C-shaped shear connectors. The application of angle shear connectors in tilted positions is of interest in this study. This study investigates the behaviour of tilted-shaped angle shear connectors under monotonic loading using experimental push out tests. Eight push-out specimens are tested to investigate the effects of different angle parameters on the ultimate load capacity of connectors. Two different tilted angles of 112.5 and 135 degrees between the angle leg and steel beam are considered. In addition, angle sizes and lengths are varied. Two different failure modes were observed consisting of concrete crushing-splitting and connector fracture. By increasing the size of connector, the maximum load increased for most cases. In general, the 135 degrees tilted angle shear connectors have a higher strength and stiffness than the 112.5 degrees type.